ҲӘЗИРГИ ҚАРАҚАЛПАҚ ӘДЕБИЯТЫНДА ФЭНТЕЗИ ЖАНРЫ ТУЎРАЛЫ - Матимов, К.Г. (FAN va JAMIYAT, 2025)
The article discusses the theory and genesis of the fantasy genre, the sources of significant creativity and emergence of representatives of modern world literature, the stages of its formation, and the history of its development. The emergence of this genre in Karakalpak literature of the 21st century is described in the work of O. Abdirakhmanov.